2023
DOI: 10.2478/ijcm-2022-0017
|View full text |Cite
|
Sign up to set email alerts
|

Innovative work-life balance after COVID-19

Abstract: Purpose The aim of this article is to analyze the idea of work-life balance (WLB) for the new times after the COVID-19 pandemic from the perspective of organizations, and to indicate an innovative approach to the implementation of WLB tools. The main scientific problem is: What innovations in the field of work-life balance do parents expect from contemporary organizations as a result of experiences related to the COVID-19 pandemic? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Managers work longer hours, placing high demands on themselves as managers, and remain almost constantly available, often driven by fear of losing control. This is particularly concerning because as the research of Marzec et al (2023) has shown, as the amount of time dedicated to work increases, satisfaction with the performance of professional duties decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Managers work longer hours, placing high demands on themselves as managers, and remain almost constantly available, often driven by fear of losing control. This is particularly concerning because as the research of Marzec et al (2023) has shown, as the amount of time dedicated to work increases, satisfaction with the performance of professional duties decreases.…”
Section: Discussionmentioning
confidence: 99%